Nutrient loss in runoff and growth response of immature oil palm following application of controlled-release fertilizers - Bah, Alagie (2015)
Implementation of sound fertilizer management program in the tropics is essential in optimizing production and economic returns. Controlled-release fertilizers (CRFs) are intended to supply plant nutrients in synchrony with crop demand, which should ultimately minimize nutrient loss from crop fields. Studies on the fate and plant response of CRFs in tropical oil palm agro-ecological fields are still lacking. In this study, a one-year field trial was established to investigate whether application of CRFs rather than conventional water-soluble mixture fertilizer can reduce nutrient loss and enhance growth of oil palm at the immature stage. Soil and nutrient loss were monitored in 2012/2013 under erosion plots of 16 m2 each planted with immature old oil palm tree on a 10% slope gradient. Fertilizer treatments applied included granular and briquette forms of CRFs (AJIB® CRF) in 100% and 60% dosages, a conventional mixture fertilizer in 100% dosage and an unfertilized control. Water Erosion Prediction Project (WEPP) model was also used to predict runoff and soil erosion from the study field. On an annual basis, mean sediments concentration in runoff amounted to about 6.41 t ha-1. On average, total captured runoff as percentage of annual rainfall amounted to 14 %, with yearly total rainfall events of 219 days. Nutrient loss was higher from mixture fertilizer treatments than those treated with CRF. Runoff loss of N was greater (p=≤0.001) in plots that received conventional mixture fertilizer, amounting to 7% of ammonium sulfate-N applied, and that with CRF application accounted for between 1- 2% N loss. Runoff P losses were usually lower for all fertilized treatments than unfertilized control. Large runoff losses of K (13%) and Mg (15%) were observed in plots that received mixture fertilizer. However, runoff losses of K and Mg from applied CRFs were in the range of 4-7%. Meanwhile, runoff process exported less sedimentassociated nutrients, ranging from 0.39-0.93 kg N, 0.15-0.31 kg P, 1.03-2.14 kg K and 0.17-0.29 kg Mg ha-1 yr-1 in fertilized plots. Total yearly precipitation, number of rainfall events and soil loss were predicted fairly well by the WEPP model with a mean difference of 2% and 4% and 15%, respectively. However, the actual and simulated yearly runoff volume differed by 36%. Also, the WEPP model showed good tendency to predict monthly precipitation (r2 = 0.57), rainfall days (r2 = 0.79) and soil erosion (r2 = 0.62). Prediction of monthly runoff was less accurate (r2 = 0.32). Plant growth parameters such as frond number and bole diameter were significantly greater with granular CRF (100%) than the control and mixture treatments. In conclusion, CRFs proved effective in maintaining robust oil palm growth and in reducing runoff associated nutrient loss compared to mixture fertilizer. This could be attributed to the fact that nutrient elements in CRFs are readily and slowly available for plant uptake over a given period.